Possible involvement of Opioid like Receptor1 (ORL1) Receptor in Ischemic Preconditioning Induced Protection in Rat Brain - Singh, Anjali; Kumar, Neeraj; Semwal, Bhupesh C.; Yadav, Harlokesh N. (Journal of Drug Delivery and Therapeutics, 2019)
Opioid receptor like 1 receptor (ORL1) is a family of G-protein coupled receptor, reported to produce cardio-protection against ischemia- reperfusion induced injury in rat heart. The present study has been designed to investigate the role of ORL1 receptor in ischemic preconditioning (IPC) induced protection in rat brain. IPC was induced by giving 3 episodes of ischemia and reperfusion. Global ischemia for 17 min was given by occlusion of carotid artery followed by 24hr of reperfusion. Memory was assessed by measuring escape latency time (ELT) for consecutively 4 days and time spent in target quadrant (TSTQ) was measured on 5th day by using morrish water maze. IPC significantly decrease in infarct size and improvement in memory as compared to ischemia/reperfusion (I/R) in control group. Pretreatment with JTC-801(1mg/kg, i.p.), a selective ORL1 receptor antagonist or Glibenclamide (1mg/kg, i.p.), the KATP channel blocker significantly reduce the amplitude of IPC induced cerebroprotection measured in terms of infarct size and positively affects the memory measured in terms of time spent in target quadrant (TSTQ) at 5th day as compare to IPC group. The cerebroprotective effect of IPC was significantly attenuated in JTC-801 and Glibenclamide in combination as compare to Ischemic preconditioning (IPC) group and treated group (Glibenclamide). These results may indicate that cerebroprotective effect of IPC of brain and improvement of memory mediated through ORL1 receptor and activation of KATP channels. Keywords: Opioid receptor like1 receptor, ischemic preconditioning, JTC-801, latency time